EKSPLOITASI DAN KETIMPANGAN PERLINDUNGAN SOSIAL BAGI PEKERJA MIGRAN INDONESIA DI KAMBOJA: PERSPEKTIF KEADILAN SOSIAL DAN KESEJAHTERAAN - Kisbiyah, Sasqhia Laillyah; Auly, Zaskia Putri; Cahya, Kartika Dwi; Simanjuntak, Azra Nusa Ananta; Mubarok, Ahmad Zaky; Ishaq, Raden Muhammad Maulana (Jurnal Multidisipliner Kapalamada, 2025)
This study discusses the exploitation and inequality of social protection experienced by Indonesian migrant workers (PMI) in Cambodia, with a perspective of social justice and welfare. While there are more than 131,000 migrant workers working legally in Cambodia, about 80,000 others work illegally in sectors vulnerable to exploitation, such as online gambling and online fraud. This condition puts migrant workers in a particularly vulnerable position to human rights violations, including human trafficking, physical violence, and injustices in wages and working conditions. This study uses a qualitative approach through case studies to analyze the social protection inequality experienced by migrant workers, by examining the real conditions they face. The findings show that weak legal protection systems in both Indonesia and Cambodia exacerbate this inequality. The study suggests the need for stronger bilateral cooperation and strengthening of protection systems for migrant workers, including better migration education in their areas of origin.